HOUSING AND INTEGRATING REFUGEES: SOUTH AFRICA’S EXCLUSIONARY APPROACH - Callixte Kavuro (Obiter, 2019)
The article seeks to illuminate South Africa’s exclusionary approach towards housing refugees and asylum seekers, and to integrating them into the economy. To this end, this article argues that the exclusionary approach conflicts with and is in violation of the constitutional values of human dignity, equality and freedom on which South Africa’s refugee law is based. The article employs a qualitative research methodology to illustrate that policy issues are acting as barriers to accessing housing programmes. It makes recommendations on how to close the gaps in housing law to ensure that future planning and implementation of housing policies are in harmony with refugee policies. Finally, innovative and creative solutions to the challenges that refugees and asylum seekers face in the housing sector are drawn from the learning processes acquired from past experience.